Penerapan Sistem Informasi Manajemen Pendidikan pada TPQ Zainul Hasan Desa Pasembon Kotaanyar Probolinggo - Muhammad Ainul Yaqin; Ulfa Diana; Ainayatul Kholila (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
The education management information system or SIMDIK is an information system used for the management needs of educational institutions. Along with the rapid development of information technology, researchers are aware of the importance of the need for an information technology-based management information system mechanism. The purpose of this study was to analyze the extent to which an education management information system was implemented at TPQ Zainul Hasan, Pasembon Village, Kotaanyar Probolinggo and to obtain data on the benefits of implementing an education management information system on the institutional environment at TPQ Zainul Hasan. The research method used is descriptive qualitative. Data collection methods used are observation, interviews and documentation. The data analysis technique that the researcher uses is qualitative analysis by means of data reduction and data presentation. The results obtained are that TPQ Zainul Hasan has utilized all the facilities or infrastructure that support the implementation of an education management information system known as EMIS, so that specifically with the development of this education management information system, it can provide improved educational services including helping facilitate data management. related to the institution and is an interactive medium between the institution and the guardian of students.